O gerenciamento de riscos no ??mbito do portf??lio de projetos: a influ??ncia nos resultados - Zanfelicce, Ricardo Luis (2018)
The intense competition, frequent market changes and fast technological advances force the organizations to run several projects to implement their strategic plans. Due to resource constraints, only the projects more aligned with the corporate strategy should be incorporated into the portfolio in order to be executed. The portfolio management must ensure the continuity of the most suitable projects during the portfolio life cycle, in order to reach the strategic objectives with an acceptable risk level to the organization. Therefore it??s necessary to manage the portfolio risks. However, practical results have shown that projects are still not reaching their goals, and portfolios, in general, are not successful, jeopardizing the implementation of organizations' strategic planns. Through a specific case study, developed in an industrial company, it was possible to interpret how risk management influences the project portfolio success. The results corroborate with the analyzed literature regarding the contribution of risk management to the project portfolio success. However, risk management remains a complex issue, in part due to the lack of knowledge by practitioners, despite its importance. The research showed that managing risks at the project level helps them to achieve their objectives and not integrating risk management into portfolio management processes influences the organization to allocate resources to inadequate projects, not implementing its strategic plan entirely. From the academic side, it was possible to advance to the subject understanding through the in-depth study of a portfolio subjected to uncertainty conditions. The results indicated that it is complex to determine the intensity with which the risk management is integrated in the portfolio management processes. Methodologically speaking, the use of content analysis allowed to reduce the researcher??s influence in the data analysis. For practitioners, the research confirmed that managing risks still causes fear due to lack of knowledge of the subject, but not manage the risks brings negative results for both projects and portfolio. In addition, it raised the issue of how to manage portfolio risks, since the portfolio is managed at a more strategic and less operational level.